Magnetic mesoporous silica loaded with CGRP antagonist and curcumin coated with cerium oxide for the treatment of neuropathic pain - Yue Tian; Lei Wei; Liangliang Gao; Yi Zhu; Zhuoliang Zhang; Xinyu Lu; Yinhong Jiang; Chengyong Gu; Chenghuan Shi; Huibin Su (Journal of Materials Science: Materials in Engineering)
Abstract Neuropathic pain is chronic pain caused by damage or dysfunction of the nervous system. Pro-inflammatory factors and abnormal reactive oxygen species (ROS) production in the spinal cord play a key role in the occurrence and development of neuropathic pain. Current treatments for neuropathic pain have limited efficacy. In this study, we prepared a nano-enzyme functionalized and magnetically targeted cerium oxide multidrug system (FMCCC), which was able to be coated by microglial BV2 cells and effectively inhibited LPS-induced microglial inflammation, which resulted in the increase of inflammatory factors, oxidative stress, and reactive oxygen species (ROS) production. In a mouse model of chronic compression injury of the sciatic nerve, FMCCC significantly improved mechanical hyperalgesia, inhibited inflammatory factors and oxidative stress, and eliminated ROS. In summary, FMCCC can relieve neuropathic pain by promoting magnetic targeting to the nerve compression site, releasing neurotherapeutic drugs Cur and peptides, and eliminating ROS, oxidative stress, and inflammatory factors, which provides a new idea for the treatment of neuropathic pain.